2012
DOI: 10.1210/me.2011-1383
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocarcinogenesis in FXR−/− Mice Mimics Human HCC Progression That Operates through HNF1α Regulation of FXR Expression

Abstract: Farnesoid X receptor (FXR) (nuclear receptor subfamily 1, group H, member 4) is a member of nuclear hormone receptor superfamily, which plays essential roles in metabolism of bile acids, lipid, and glucose. We previously showed spontaneously hepatocarcinogenesis in aged FXR(-/-) mice, but its relevance to human hepatocellular carcinoma (HCC) is unclear. Here, we report a systematical analysis of hepatocarcinogenesis in FXR(-/-) mice and FXR expression in human liver cancer. In this study, liver tissues obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 35 publications
(26 reference statements)
4
110
2
Order By: Relevance
“…The level of SHP expression was much lower in aging FXR -/-mice with HCC compared to young FXR -/-mice [19] . In human HCC specimens, expression of FXR and SHP are both markedly decreased [23,25] , and the FXR mRNA level was significantly and positively correlated with the SHP mRNA level in HCC tissues [23] . Those studies demonstrate that loss of SHP may contribute to liver carcinogenesis in livers deficient in FXR.…”
Section: Fxr-regulated Target Genes and Liver Cancermentioning
confidence: 93%
See 2 more Smart Citations
“…The level of SHP expression was much lower in aging FXR -/-mice with HCC compared to young FXR -/-mice [19] . In human HCC specimens, expression of FXR and SHP are both markedly decreased [23,25] , and the FXR mRNA level was significantly and positively correlated with the SHP mRNA level in HCC tissues [23] . Those studies demonstrate that loss of SHP may contribute to liver carcinogenesis in livers deficient in FXR.…”
Section: Fxr-regulated Target Genes and Liver Cancermentioning
confidence: 93%
“…The elevated levels of proinflammatory cytokines, such as TNFα, IL-1β, and IL-6, in both FXR -/-mice [19,20] and in most human HCC patients [25,88] , may reduce the FXR expression via inhibiting the transactivity of hepatic nuclear factor 1α (HNF1α) on the FXR gene promoter [25] . TNFα and IL-1β alter the relative expression of FXRα1 and FXRα2, which leads to an increase in the FXRα1/ FXRα2 ratio and subsequent reduction of BSEP, indicting a potential interaction between FXR alternative splicing procedure and the inflammatory-cytokine mediated signal pathway [88] .…”
Section: Downregulation Of Fxr Expression In Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…FXR knockout mice have been shown to develop liver tumours with aging [69,70], and FXR expression has been found to be signifi cantly decreased in many human tumour specimens [71][72][73][74]. In FXR knockout mice excessive BA accumulation has been considered to have cytotoxic effects, thus favouring tumorigenesis [69,70,75].…”
Section: Anti-tumorigenic Propertiesmentioning
confidence: 99%
“…Since two independent groups reported that the loss of FXR in Fxr-null mice resulted in spontaneous hepatocarcinogenesis [7,8], considerable research efforts have been focused on the identification of the underlying mechanisms of liver cancer inhibition by FXR and its relevance in the pathogenesis of human HCC. Subsequently, it has shown that FXR expression in human HCC samples was decreased compared to normal liver tissues [9].…”
Section: Introductionmentioning
confidence: 99%